Development of Smart Apps Creator-Based Interactive Chemistry Learning Media Integrated with Discovery Learning for Acid-Base Topics - Afriani Br Hombing; Ricky Andi Syahputra (Hydrogen: Jurnal Kependidikan Kimia, 2026)
This study aimed to develop Smart Apps Creator (SAC) based interactive chemistry learning media integrated with the Discovery Learning model for acid-base topics and to determine the validity and practicality. This study employed Research and Development (R&D) method with the 4D development model consisting of Define, Design, Develop, and Disseminate stages. The research participants included 3 expert validators, 2 chemistry teachers, and 36 students of class XI-7 at SMA Negeri 13 Medan. Data were collected through interview guidelines, expert validation sheets, and teacher and student response questionnaires. The results showed that the developed media obtained an overall validation score of 87%, consisting of 84% from material experts and 88% from media experts, indicating that the media was very feasible. Teacher and student responses reached 92% and 85%, respectively, indicating that the media was very practical for classroom implementation. Therefore, the developed learning media is considered valid and practical for acid-base instruction. However, further research is needed to examine its effectiveness in improving students’ conceptual understanding and learning outcomes.